(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study determined the utilization of instructional materials in teaching and learning of business studies in secondary schools in Anambra State. Two research questions guided the study and two null hypotheses were. Descriptive survey research design was adopted for the study. The population of the study comprised 296 business subject teachers in all public secondary schools in Anambra State. A five point rating scale questionnaire which was validated by experts was used for data collection. Cronbach alpha was used to test the reliability of the instrument and reliability index of .82 was obtained. Data collected from the study were analyzed using mean and standard deviation to answer the research questions and ascertain the homogeneity of the respondents while Analysis of Variance (ANOVA) was used to test the hypotheses at 0.05 level of significance. The results showed that the business studies teachers seldomly utilized projected visual instructional materials and often utilized non-projected visual instructional materials in teaching. The findings further revealed that teachers did not differ significantly in their mean ratings based on years of experience.It was concluded that utilization of instructional materials by business studies teachers should help secondary school students acquire entrepreneurial skills that will enable them to be self-sufficient in the competitive world of work. Based on the findings, the researchers recommended, among others, that relevant authorities should organize seminars, in-service training, conferences and workshops for business studies teachers on the utilization of instructional materials for effective learning outcomes.